Chitosan Based Materials in Cosmetic Applications: A Review - Karolina Kulka; Alina Sionkowska (Molecules, 2023)
This review provides a report on the properties and recent advances in the application of chitosan and chitosan-based materials in cosmetics. Chitosan is a polysaccharide that can be obtained from chitin via the deacetylation process. Chitin most commonly is extracted from cell walls in fungi and the exoskeletons of arthropods, such as crustaceans and insects. Chitosan has attracted significant academic interest, as well as the attention of the cosmetic industry, due to its interesting properties, which include being a natural humectant and moisturizer for the skin and a rheology modifier. This review paper covers the structure of chitosan, the sources of chitosan used in the cosmetic industry, and the role played by this polysaccharide in cosmetics. Future aspects regarding applications of chitosan-based materials in cosmetics are also mentioned.